1994
DOI: 10.1007/bf00348234
|View full text |Cite
|
Sign up to set email alerts
|

Laser-ionization mass-spectrometric studies on laser ablation of a nitrogen-rich polymer at 532 nm and 1064 nm

Abstract: Abstract. Laser-ionization Time-Of-Flight (TOF) massspectrometric studies have been carried out on the 532 nm and 1064nm laser ablation products from a nitrogen-rich polymer. The polymer used had an elemental composition of C6.oNs.9H3. 4 and consisted of C = N , C --N , and N --H chemical bonds. The TOF mass spectra observed were composed of various peaks (_< 150 amu) depending on the ablation laser wavelength. The primary peaks were assigned to C +, CN +, CH,N (n = 1 -3) and C2H2N ;-for 532 nm ablation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Such strong emissions of HCl from PVC by laser or heating is in agreement with many other studies. [11][12][13] They have shown that the thermal degradation of PVC proceeds in the following two stages. The first stage proceeds in the temperature range of 470 to 640 K. It corresponds to dehydrochlorination with the subsequent formation of conjugated double bonds, as shown in Fig.…”
Section: Mass Spectroscopymentioning
confidence: 99%
“…Such strong emissions of HCl from PVC by laser or heating is in agreement with many other studies. [11][12][13] They have shown that the thermal degradation of PVC proceeds in the following two stages. The first stage proceeds in the temperature range of 470 to 640 K. It corresponds to dehydrochlorination with the subsequent formation of conjugated double bonds, as shown in Fig.…”
Section: Mass Spectroscopymentioning
confidence: 99%
“…Mass spectrometric studies have been performed on various polymers under various conditions, e.g., as a function of irradiation wavelength and laser fluence [213]. Analysis of the ejected material has revealed ionic and neutral species with masses ranging from small degradation fragments [214,215], to the monomer (from unzipping reactions) [216,217], to carbon clusters [218], and finally to polymer fragments with molecular weights of up to 2,500 [168,219].…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometric studies have been performed on various polymers under various conditions, e.g., as a function of irradiation wavelength and laser fluence. 3 Analysis of the ejected material has revealed ionic and neutral species with masses ranging from small degradation fragments, 4,5 to the monomer ͑from unzipping reactions͒, 6,7 to carbon clusters, 8 and finally to polymer fragments with molecular weights of up to 2500. 9,10 Timeof-flight ͑TOF͒ distributions ͑in reality, these are ''time-ofarrival'' curves͒ of neutral fragments have been analyzed to determine the energy distributions of the fragments.…”
Section: Introductionmentioning
confidence: 99%